(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Marketing is a strategy that focusses on the client and serves the purpose of generating money for a company over an extended period of time. For the purpose of determining what the consumers want and need and then offering it to them, it is necessary for every department inside the organisation to provide feedback. Since marketing is such a fluid profession, it is inevitable that it would go through continuous modification. This is something that one would anticipate. On the other hand, marketing is growing more significant in every organisation and in our everyday lives in some different manner. Marketing is an integrated system of activities that offers shape, place, time, and ownership utilities. Value is added to commodities via the marketing process, which is an integrated system of actions. One of the primary goals of marketing is to steer the efforts of a firm towards meeting the needs and desires of consumers. The discovery of what people want, the creation of a product that satisfies those criteria, and the subsequent determination of how to sell, promote, and distribute the product are all components of marketing and distribution strategy. However, in the actual world, marketing is not only responsible for activities such as advertising, distribution, selling, and other similar activities.